Effects of self-medication reasons, television advertisements, and pharmaceutical professionals’ roles on self-medication practices: 10.55131/jphd/2023/210215 - Agus Susanto; Heni Purwantiningrum; Meliyana Perwita Sari (Journal of Public Health and Development, 2023)
Self-medication has become increasingly common in society, and it is crucial to provide reliable information and emphasize the role of pharmacists in dispensing information to ensure that self-medication is carried out safely. This study aimed to analyse the reasons for self-medication, the influence of television advertisements, and the role of pharmacists in self-medication. The research used a descriptive-analytic approach with a cross-sectional design. The study involved 350 adult participants who were purposively selected in Tegal City, Central Java, Indonesia. Data were collected using a questionnaire and analysed using SPSS, employing univariate and bivariate analyses. The Chi-Square test was used to investigate the relationship between variables, with a significance level of 0.05. The findings showed that the primary reasons for self-medication were minor illnesses (63.1%), complete TV advertisements (86.3%), active involvement of pharmacists (68.9%), and good self-medication practices (73.1%). The study revealed that there was a significant relationship between the reasons for self-medication (p=0.032) and the role of pharmacists (p=0.002) in self-medication practices. In conclusion, the study found that self-medication practices were good, but pharmacists should be more active in providing information to clients to enhance the quality of self-medication. To achieve this, pharmacists need to play a more significant role in promoting appropriate self-medication practices by providing appropriate information on the safe use of medications. Moreover, health authorities should develop policies to regulate the advertising of over-the-counter drugs, emphasizing the risks of inappropriate use of medications through the media.